The Impact of Human Capital on Business Performance of Tourist Agencies (Journal of Universal Excellence, 2026)
Research Question (RQ): What importance do we attach to the dimensions of human capital (HC) on business performance (PU) of tourist agencies (TA)?Purpose: Examine the impact of HC on BP of TA and through a questionnaire carried out a quantitative survey in Slovenian TA.Method: The collected survey data were analyzed by the following statistical methods: descriptive analysis, factor analysis and principal component analysis, multiple regression analysis and structural equation methods.Results: In part, we confirmed only one hypothesis, namely that the dimensions of HC impact on profitability as a component of the BP of TA, and two hypotheses were rejected: impact of dimension of HC on sales growth as a component of the BP of TA and impact of dimension of HC on efficiency as a component of the BP of TA.Organization: Managers have to give a greater influence to the HC as a factor in business success.Society: To inform the owners, managers and heads of TA, as well as others that the HC is important for all stakeholders and it is necessary to promote its increasing importance.Originality: It is the first such study in Slovenia and one of the first in the world literature.Limitations / further research: The questionnaire was aimed at owners / managers / managers and other employees in the TA and their branches, but not to their business partners, which contribute greatly to quality of services in TA. Suggestions for further research are in longitudinal research, and also in the fact that in the research are also included any other country and then compare the data.
Keywords: human capital; business performance; tourism; agency